The domestication of the African elephant - Eve Iversen (Pachyderm)
Reviews the historic domestication and use of African elephants in western Zaire, the unsuccesful attempts to import Asian elephants, and the capture and training of elephants from the late 1800s through to about 1960. Notes the redevelopment of earlier forest elephant domestication in Garamba National Park, and the ongoing attempt to domesticate bush elephants in the Okavango Delta area with the assistance of circus trained animals. Tourism is the focus of both present programmes.